2020
DOI: 10.3390/ma13184054
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study on Mechanical Properties of Interface between Urea-Formaldehyde Resin and Calcium-Silicate-Hydrates

Abstract: Microcapsule based self-healing concrete can automatically repair damage and improve the durability of concrete structures, the performance of which depends on the binding behavior between the microcapsule wall and cement matrix. However, conventional experimental methods could not provide detailed information on a microscopic level. In this paper, through molecular dynamics simulation, three composite models of Tobermorite (Tobermorite 9 Å, Tobermorite 11 Å, Tobermorite 14 Å), a mineral similar to Calcium-Sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…According to the literature, in which Ca atoms are commonly selected to indicate the connection between polymers and C–S–H [ 47 ], the RDF of Ca atoms of tobermorite in the models and other atoms in the epoxy resin is shown in Figure 12 a,b. Since it is widely accepted that the position of the first peak is related to the connection between the two atoms [ 48 , 49 ], i the lower value of r indicates a stronger connection. It can be seen from the figure that the first peak of Ca T –H EX , Ca T –O EX , Ca T –C EX , and Ca T –N EX of model 5 appeared at 2.35 Å, 2.35 Å, 2.65 Å, and 3.05 Å, respectively, while model 6 appeared at 2.45 Å, 2.25 Å, 2.65 Å, and 2.35 Å, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, in which Ca atoms are commonly selected to indicate the connection between polymers and C–S–H [ 47 ], the RDF of Ca atoms of tobermorite in the models and other atoms in the epoxy resin is shown in Figure 12 a,b. Since it is widely accepted that the position of the first peak is related to the connection between the two atoms [ 48 , 49 ], i the lower value of r indicates a stronger connection. It can be seen from the figure that the first peak of Ca T –H EX , Ca T –O EX , Ca T –C EX , and Ca T –N EX of model 5 appeared at 2.35 Å, 2.35 Å, 2.65 Å, and 3.05 Å, respectively, while model 6 appeared at 2.45 Å, 2.25 Å, 2.65 Å, and 2.35 Å, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The stress-strain curve obtained by uniaxial tensile simulation is shown in Figure 9 , and the failure strain and peak stress are shown in Table 1 . As with the stress-strain curves of tobermorite or tobermorite/urea-formaldehyde resin obtained by other scholars [ 24 , 36 ], all three stress-strain curves have three stages, namely, the elastic stage (I), the yield stage (II), and the failure stage (III). As can be seen from the Figure 9 , the three models are basically the same in the elastic stage, while differences begin to appear in the yield stage.…”
Section: Resultsmentioning
confidence: 67%
“…The main factors influencing the repair effect of microcapsule-based self-healing concrete are as follows: (1) curing reaction of repair agent; (2) permeability of repair agent in crack; (3) destruction patterns of microcapsules; and (4) the bonding strength of the remediation agent on the surface of the cement matrix. In the authors’ previous studies on microcapsule-based self-healing concrete using molecular dynamics [ 24 , 25 ], the interaction between the microencapsulated shell (urea-formaldehyde resin) and core (epoxy resin) and C-S-H has been studied. The results showed that the microcapsule shell and core have good interfacial bonding energy with the surface of cement matrix, which can meet the requirements of repairing cracks.…”
Section: Introductionmentioning
confidence: 99%
“…This reduction in Young's modulus and improvement in brittleness could be attributed to the difference in stiffness of microcapsules and cementitious matrix [26,40]. Moreover, the weak interfacial behaviour between microcapsule cores and the cementitious matrix could also contribute to the change in the mechanical properties of self-healing cementitious materials [51]. Obviously, the size of the microcapsule significantly affected the mechanical properties of cement pastes.…”
Section: Effect On Mechanical Propertymentioning
confidence: 99%